Principles for the development of vacuum systems for plasma applications - Zhukeshov, A.; Gabdullina, A.; Pak, S.; Amrenova, A.; Kaibar, A.; Кulzhanova S.; Kurmanbaev, K. (Recent Contributions to Physics, 2018)
This article contains basic principles for the development of vacuum systems for use in plasma processes. Outlines the advantages of pulse plasma treatment and methods of vacuum plasma spraying. Explains the basic principles of automation and vacuum switch.